Effect of ensiling treatment on secondary compounds and amino acid profile of tropical forage legumes, and implications for their pig feeding potential. (2nd October 2013) - Martens, Siriwan D; Hoedtke, Sandra; Avila, Patricia; Heinritz, Sonja N; Zeyner, Annette
Abstract BACKGROUND Smallholders in the tropics depend on local protein supplements to balance pig diets. Thus, various tropical forage legumes are a potential feeding option. Ensiling allows converting forages into a ready‐to‐feed‐out choice, but the lactic acid fermentation may influence various (anti)nutritional components. The purpose of this study was to evaluate the effects of sucrose (SU) and a tropical Lactobacillus plantarum strain (LAB) as ensiling treatments (control, SU, LAB, LAB + SU) on the potential nutrient availability of 10 forage legume species. RESULTS Ensiling commonly reduced antinutritional compounds such as tannins (by 49–84%) and trypsin inhibitory activity (by 74–78%), as well as oxalic acid (by 51–100%). An improved potential absorbability of protein and minerals for pigs is thus inferred. There was no major loss in total amino acids. In general, the species effect was stronger than the treatment effect. A clear effect of the treatments SU, LAB and LAB + SU over all 10 forage species was only observed for oxalic acid, single amino acids and trypsin inhibitory activity. CONCLUSION Ensiling is a viable option to enhance nutrient utilization of tropical forages for pigs. Species‐specific treatment of forage legumes is recommended. © 2013 Society of Chemical Industry